The Establishment of Indonesian Securities Investor Protection Fund Related To The Supreme Court Decision No. 535.K/Pid/2013 About The Case of PT Sarijaya Permana Securities - ADIYA RIZKI KARAMI (Problematika Hukum, 2015)
Indonesia is one of the developing countries who are actively carried out their development. In the development of the national economy, a country requires financing either from the government or the community. Acceptance of the government to build a national economy gained through taxes and other admission. One of the sources government use are the community investment through bank, other financial institutions and capital markets. Capital Market in Indonesia is one of the essential elements and benchmarks of the country's economy. One of the characteristics in advanced industrial countries and new industries is the presence of capital markets growth and development. With the growth in the Capital Market, there are so many problems that occurred such as embezzlement, fraud, misuse of funds, and misuse from the irresponsible Market Intermediary. With the problems that occurred, the victim of these problem is the investor who investing their funds in Indonesian Capital Market. Lots of this problems that occurred because there is no institution directly concentrate in investor protection fund. So, the government established Indonesian Securities Investor Protection Fund (ISIPF) for protecting, controlling, monitoring, and regulating the activities that occurred in Capital Market. With the establishment of Indonesia Securities Protection Fund (ISIPF), investor that invest their funds can claim their investment if the violation occurred. With their protection, capital market in indonesia will gain more trust from domestic and foreign investor in the future.